Development and Performance Evaluation of a Real-Time Environmental Monitoring System Using ESP32, MQTT, Node-RED, and MySQL Database - MICKO TOMAS; Refki Budiman; Baharuddin; Riko Nofendra; Hanalde Andre; Elsi Alfionita (Electrical Engineering Department Faculty of Engineering Universitas Andalas, 2026)
Real-time environmental monitoring is an important requirement for managing facilities, laboratories, server rooms, and work environments that require temperature and humidity control. This study aims to develop and evaluate the performance of an Internet of Things (IoT)-based environmental monitoring system using ESP32 microcontrollers, DHT11 sensors, the Message Queuing Telemetry Transport (MQTT) protocol, Node-RED, and a MySQL database. The system is designed to acquire temperature and humidity data, transmit data via Wi-Fi using MQTT, display real-time measurement results on the Node-RED dashboard, and store historical data into a MySQL database. Testing was carried out with a data transmission interval of every 5 seconds using MQTT QoS 0. The test results showed that the system was capable of continuous monitoring, with a measured temperature range of 27.1–28.5 °C and a relative humidity range of 44–51% RH. Sensor data was successfully transmitted, visualized, and stored in real-time without any loss of observed data during the test period. The Node-RED dashboard can display information as gauges, trend graphs, and historical tables, facilitating the monitoring and analysis of environmental data. The integration of ESP32, MQTT, Node-RED, and MySQL produces a stable, low-cost, easy-to-develop monitoring system with potential for implementation in various IoT-based environmental monitoring applications. The results of the study indicate that the proposed architecture can provide a reliable environmental monitoring solution and support real-time, data-driven decision-making.